ChemInform Abstract: A Traceless Directing Group for C—H Borylation. Issue 20 (20th May 2014) - Preshlock, Sean M.; Plattner, Donald L.; Maligres, Peter E.; Krska, Shane W.; Maleczka, Robert E. Jr.; Smith, Milton R. III
Abstract A strategy is described for the regioselective substitution of a variety of N‐unsubstituted N‐heterocycles with HBpin.